1985
DOI: 10.1002/ana.410180306
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the nucleus basalis in Down's syndrome

Abstract: One of the most striking manifestations of Down's syndrome is profound mental retardation. Furthermore, after 35 years of age, many patients with Down's syndrome develop clinical and pathological features of Alzheimer's disease. Since brains of patients with Alzheimer's disease show significant loss of neurons in the nucleus basalis of Meynert (nbM), we sought to establish normal standards of nbM neurons in persons with Down's syndrome and to determine whether reductions in the number of neurons occur with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
93
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(97 citation statements)
references
References 13 publications
4
93
0
Order By: Relevance
“…These reductions are analogous to the loss of forebrain cholinergic neurons seen in both Down syndrome (Casanova et al, 1985;Head et al, 2001;Mann and Esiri, 1989) and Alzheimer's Disease (Candy et al, 1986;Coyle, Price and DeLong, 1983;Vogels et al, 1990;Whitehouse et al, 1985).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…These reductions are analogous to the loss of forebrain cholinergic neurons seen in both Down syndrome (Casanova et al, 1985;Head et al, 2001;Mann and Esiri, 1989) and Alzheimer's Disease (Candy et al, 1986;Coyle, Price and DeLong, 1983;Vogels et al, 1990;Whitehouse et al, 1985).…”
Section: Introductionmentioning
confidence: 81%
“…Prior findings indicate that some markers of ACh function in Ts65Dn mice are intact at young ages but emerge in adulthood, generally evident after 6 months of age (Granholm, Sanders and Crnic, 2000). The development of cholinergic dysfunctions in Ts65Dn mice parallels a similar situation in humans with Down syndrome, in whom the basal forebrain cholinergic system appears normal at birth but degenerates in early adulthood (Casanova et al, 1985;Head et al, 2001;Yates et al, 1983). The cholinergic neurons that project to the hippocampus and provide the source of the ACh release measured in the present experiment are located in the medial septum.…”
Section: Acetylcholine Releasementioning
confidence: 88%
See 1 more Smart Citation
“…In addition, in the present study, an increased density of senescent cells was not only observed in the hippocampus but also in the septum and cingulate cortex of TS +/+/+ mice, and reducing the number of functional copies of Dyrk1A completely rescued this phenotype in these three structures. The septo-hippocampal cholinergic system in learning and attention (Bartus, 2000;Baxter and Chiba, 1999) and this population of neurons undergoes atrophy and degeneration in both AD and aging DS individuals (Mufson et al, 2003;2000;Risser et al, 1997;Casanova et al, 1985;Godridge et al, 1987). In addition, the cingulate cortex and hippocampus, also implicated in learning and AD-related cognitive loss, present the increased accumulation of Aβ oligomers during disease progression (Serrano-Pozo et al, 2011).…”
Section: Dyr1ka and Cellular Senescencementioning
confidence: 99%
“…The abnormalities include shorter life expectancies and morphological, neurological, behavioral, structural, and neuronal circuit abnormalities that parallel those in people with DS [8][9][10][11][12][13][14][15]. Furthermore, consistent with the changes demonstrated in imaging and behavioral studies in people with DS [5][6][7], the Ts65Dn model displays deficits in hippocampal structure and function. These changes include deficits in synaptic plasticity, as demonstrated in cellular signaling and electrophysiological studies [8,9,[22][23][24][25][26].…”
mentioning
confidence: 81%